Discrepancy between performance and feedback affects mathematics student teachers’ self-efficacy but not their self-assessment accuracy - Ernst, Helen M.; Prinz-Weiß, Anja; Wittwer, Jörg; Voss, Thamar (Frontiers in Psychology, 2025)
Although feedback is of high importance for the professional development of student teachers, the impact of (inadequate) feedback on their self-regulated learning is still unclear. In two studies with mathematics student teachers, we investigated how discrepancies between performance and feedback affected two important aspects of self-regulated learning—self-efficacy and self-assessment accuracy regarding mathematical content knowledge. In the first study, N = 154 student teachers studying mathematics completed a knowledge test on the Pythagorean theorem and received performance feedback that was either correct or manipulated to be more positive or more negative than actual performance. The results showed that feedback that exceeded performance resulted in higher self-efficacy than feedback that fell below performance. In contrast, self-assessment accuracy in a second test on the same content was not affected by the discrepancy between student teachers’ test performance and the feedback they received. In the second study, we used the think-aloud method with N = 26 participants to investigate the processes underlying the effects obtained in Study 1. We found that student teachers who had received overly positive feedback were more likely to report positive affect-related statements than participants who had received overly negative or correct feedback. At the same time, they based their self-assessments in the knowledge test more strongly on their monitoring of heuristic factors than on knowledge. The results indicate that overly positive feedback elicits positive motivational states in mathematics student teachers, but bears the risk that they neglect their knowledge as a basis for their self-assessments.